2017
DOI: 10.5152/iao.2017.3054
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between the use of Melatonin and A Solution with Melatonin, Tryptophan, and Vitamin B6 as an Inducer of Spontaneous Sleep in Children During an Auditory Response Test: An Alternative to Commonly Used Sedative Drugs

Abstract: MATERIALS and METHODS:In total, 748 children aged between 12 and 48 months were included in the study and divided into three groups: A: placebo (n=235), B: melatonin (n=246), and C: melatonin, tryptophan, and vitamin B6 (n=267). RESULTS:In groups B and C, in addition to physiological awakening, we observed a significant reduction in the number of repeated analyses as well as drug regimen usage. CONCLUSION:This study confirms the strategic role of melatonin as an inducer of spontaneous sleep. However, above all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In a pilot study [ 140 ] on children aged 7 to 17 years, melatonin supplementation (“ME group”) was compared to melatonin + vitamin B6 + Trp supplementation (“MET group”): after two months of supplementation, a statistically significant reduction of the number of night awakenings was found in the “MET group”, but not in the “ME group”. Similar results were found by another study [ 141 ] conducted on a large sample of younger children (748 patients aged 12 to 48 months) that had to undergo audiologic testing requiring the child to be asleep. A solution containing melatonin, Trp and vitamin B6 proved to be significantly more effective than melatonin alone in reducing the number of tests that had to be repeated due to awakening of the child.…”
Section: Oral Over-the-counter Medicinessupporting
confidence: 88%
“…In a pilot study [ 140 ] on children aged 7 to 17 years, melatonin supplementation (“ME group”) was compared to melatonin + vitamin B6 + Trp supplementation (“MET group”): after two months of supplementation, a statistically significant reduction of the number of night awakenings was found in the “MET group”, but not in the “ME group”. Similar results were found by another study [ 141 ] conducted on a large sample of younger children (748 patients aged 12 to 48 months) that had to undergo audiologic testing requiring the child to be asleep. A solution containing melatonin, Trp and vitamin B6 proved to be significantly more effective than melatonin alone in reducing the number of tests that had to be repeated due to awakening of the child.…”
Section: Oral Over-the-counter Medicinessupporting
confidence: 88%
“…Three different dosages were tested: two different administration timings (pre-treatment and single shot treatment) and three dosages (0.5 ml, corresponding to 1 mg of melatonin, in pre-treatment, 1.5 ml, corresponding to 3 mg of melatonin, in pre-treatment, and 3 ml, corresponding to 6 mg of melatonin in single shot). The authors found a more rapid induction of sleep using pre-medication with 1.5 ml solution (3 mg of melatonin), with a reduction in the duration of the exam [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in fatigue post pyridoxine may be linked to the fact that pyridoxine plays a vital role in haemoglobin-the protein that carries oxygen round the body-synthesis. Besides feeling tired from anemia, pyridoxine deficiency could also potentially contribute to tiredness due to its role in making the sleep-promoting hormone melatonin (25)(26).…”
Section: Discussionmentioning
confidence: 99%